Peningkatan Pendidikan: Pelatihan Bahasa Inggris dan BTQ untuk Anak Sekolah Dasar di Desa Barugae - Imma, Nur Anisma; Pratiwi, Annisa (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
In today’s globalized world, proficiency in English and religious knowledge are essential for children to succeed in both their education and personal lives. In an effort to enhance the educational landscape of Barugae Village, a program has been implemented to equip elementary school children with a unique combination of academic and religious instruction. The aim of this training is to foster learning interest and improve the quality of BTQ (Reading and Writing Al-Qur'an) skills as well as English language abilities among elementary school students in Barugae Village, Mallawa Subdistrict, Maros Regency. The implementation of this community service involved several stages, namely observation, training, and evaluation. The training or tutoring sessions were conducted successfully and smoothly in accordance with the planned activities. The initiative was met with a highly positive response, as evidenced by the students' active participation in the training sessions.